2003
DOI: 10.1590/s0103-90162003000200010
|View full text |Cite
|
Sign up to set email alerts
|

Alcobaça allele and genotypic backgrounds affect yield and fruit shelf life of tomato hybrids

Abstract: Post-harvest shelf life of tomato fruit may be increased by deploying mutant alleles which affect the natural ripening process and/or by a favorable genotypic background. Among the several ripening mutant genes, alcobaça (alc) has proved to be highly efficient in increasing shelf life of commercial tomato fruits, especially in heterozygosis, a state at which no limiting deleterious effects upon fruit color occur. The effects of heterozygosity in the alcobaça locus (alc + /alc) on yield and fruit quality traits… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…Fruit firmness is usually directly propositional to fruit shelf life, and these mutants have low pectolytic activity (Kopeliovitch et al, 1979). Rodriguez et al (2010) have recorded similar findings in the F 1 cross ca x nor, and Dias et al (2003) have found that the F 1 ('TOM591' x 'Mospomorist') alc + /alc genotype improves the rate of fruit firmness to 8.6128 N/m 2 compared with that in the parents and contributes to an increase in post-harvest shelf life.…”
Section: Phenotypic Characterizationmentioning
confidence: 61%
“…Fruit firmness is usually directly propositional to fruit shelf life, and these mutants have low pectolytic activity (Kopeliovitch et al, 1979). Rodriguez et al (2010) have recorded similar findings in the F 1 cross ca x nor, and Dias et al (2003) have found that the F 1 ('TOM591' x 'Mospomorist') alc + /alc genotype improves the rate of fruit firmness to 8.6128 N/m 2 compared with that in the parents and contributes to an increase in post-harvest shelf life.…”
Section: Phenotypic Characterizationmentioning
confidence: 61%
“…We also do not know if LA0716 flowers are sensitive to ethylene, because flower responses were not evaluated in this accession. S. lycopersicum 'OH981067' and 'Seleccion Mallorquin' have mutations in the Nac Nor gene, which confers low ethylene sensitivity and extended shelf life in fruit (Dias et al, 2003;Kopeliovitch et al, 1980). In other studies, fruit from these plants were shown to be less ethylene-sensitive, but leaf evaluations were not reported.…”
Section: Discussionmentioning
confidence: 99%
“…The LSL phenotype has been related to the alc mutation (e.g., Kopeliovitch et al, 1981;Lobo et al, 1984;Mutschler, 1984a;Casals et al, 2012;Conesa et al, 2014), described in the 'Alcobaça' landrace (Almeida, 1961;Leal and Tabim, 1974). First reports for shelf-life in 'Alcobaça' were up to 316 days (Leal and Tabim, 1974), although further reports are considerably shorter (up to 33 days; Kopeliovitch et al, 1980;Mutschler 1984b;Mutschler et al, 1988;Mutschler et al, 1992;Dias et al, 2003). The alc mutation is present in 'de Penjar' from Catalonia and Valencia and 'de Ramellet' from the Balearic Islands (Casals et al, 2012;Bota et al, 2014).…”
Section: Genetic Basis Of the Lsl Phenotypementioning
confidence: 99%